2020
DOI: 10.1109/access.2020.3007932
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Estimation of Lithium-Ion Battery Based on an Improved Magnetic Nanoparticle Thermometer

Abstract: Lithium-ion batteries are widely used in new energy vehicles, especially electric vehicles. Temperature estimation is very important for battery life and safety. However, current temperature measurement methods cannot accurately measure the battery internal temperature. In this paper, a new method for battery temperature estimation based on an improved magnetic nanoparticle thermometer (MNPT) is proposed. The influence of dc magnetic field on temperature accuracy of a MNPT is firstly studied, the optimal dc ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Temperature-sensitive properties not involving the use of ionizing radiation include amplitude 20,[24][25][26] or phase 16,27 of one of the higher-order harmonics of the magnetization signal, the ratio between harmonics of the same signal, 19,28,29 the relaxation time of nanoparticles, 30 the viscosity of the host medium, 31 the proton resonance frequency or relaxation time as in MRI thermometry, 32 various ultrasonic properties. 14 Some techniques are applied in non-biological environments as well, as for instance in vehicle batteries 33,34 Measuring the temperature via the reversible changes of the magnetic properties of the same nanoparticles used to heat a tissue (mainly through the harmonics of the picked-up signal as in MPI/ MPS) is possibly the prevalent and most direct strategy, 16,19,20,[24][25][26][27][28][29] and one which can be equally applied to particles oating in a uid environment or rmly blocked in a tissue. However, operating frequencies typical of MPI/MPS do not match the ones needed to obtain a good heating performance, so that making use of just one frequency 26 to combine thermometry and hyperthermia may result in a non-optimal heating process.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature-sensitive properties not involving the use of ionizing radiation include amplitude 20,[24][25][26] or phase 16,27 of one of the higher-order harmonics of the magnetization signal, the ratio between harmonics of the same signal, 19,28,29 the relaxation time of nanoparticles, 30 the viscosity of the host medium, 31 the proton resonance frequency or relaxation time as in MRI thermometry, 32 various ultrasonic properties. 14 Some techniques are applied in non-biological environments as well, as for instance in vehicle batteries 33,34 Measuring the temperature via the reversible changes of the magnetic properties of the same nanoparticles used to heat a tissue (mainly through the harmonics of the picked-up signal as in MPI/ MPS) is possibly the prevalent and most direct strategy, 16,19,20,[24][25][26][27][28][29] and one which can be equally applied to particles oating in a uid environment or rmly blocked in a tissue. However, operating frequencies typical of MPI/MPS do not match the ones needed to obtain a good heating performance, so that making use of just one frequency 26 to combine thermometry and hyperthermia may result in a non-optimal heating process.…”
Section: Introductionmentioning
confidence: 99%
“…Each different type of method has its advantages and limitations 53–57 . Therefore, a summary of all the prominent techniques would be very helpful to researchers and developers serving as a baseline for further research and as a guideline for selecting appropriate techniques suitable for a specific requirement 58–62 . However, such a summary with detailed discussion on current progress and explanation of the principles, applications, challenges, and future research scopes has not yet been presented in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…[53][54][55][56][57] Therefore, a summary of all the prominent techniques would be very helpful to researchers and developers serving as a baseline for further research and as a guideline for selecting appropriate techniques suitable for a specific requirement. [58][59][60][61][62] However, such a summary with detailed discussion on current progress and explanation of the principles, applications, challenges, and future research scopes has not yet been presented in the literature. Therefore, this article covered the research gap by conducting a comprehensive review of the state-of-theart temperature prediction strategies using EIS reported in the literature so far.…”
Section: Introductionmentioning
confidence: 99%
“…In [25], a fast non‐destructive method of magnetic field monitoring is introduced for detecting defects such as capacity fade and mechanical degradation inside a cell. Beside analysing the defects, magnetic field around the lithium‐ion cell has also provided useful information for temperature estimation in LIBs [26]. There are two main sources for the magnetic fields around the lithium‐ion cell: (1) surface currents in the electrode, and (2) charge transfer currents in the electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…There are two main sources for the magnetic fields around the lithium‐ion cell: (1) surface currents in the electrode, and (2) charge transfer currents in the electrolyte. The behaviour of these currents in a cell determines the magnetic field around a cell as is shown in [26], which provides significant insight of the cell operational state.…”
Section: Introductionmentioning
confidence: 99%